1997
DOI: 10.1038/sj.ejcn.1600400
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center comparison of dual energy X-ray absorptiometers: In vivo and in vitro soft tissue measurement

Abstract: Objective: To assess intra-and inter-site soft tissue variability by dual energy X-ray absorptiometry (DXA). Design: Cross-sectional trial. Setting: Three medical research institutions. Subjects: Five humans (in vivo) and four phantoms (in vitro), con®gured from two whole body phantoms with arti®cial skeletons and thickness overlays. Interventions: Duplicate total-body DXA scans were performed on all subjects at each institution within a 15 d period.Results: All intra-site coef®cients of variation (CV) were`0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 38 publications
5
22
0
Order By: Relevance
“…Elsewhere, and also using the more recent iDXA model, precision for TBL measurements have also been reported as excellent, with CVs of 0.4% (Rezzi et al, 2009), 0.52% (Faulkner et al, 2006) and 0.55% (Krueger et al, 2006).We also found excellent precision for the measurement of BMC, TBF and %TBF, compared with values reported elsewhere for older models of DXA and in a range of participants (Economos et al, 1997;Figueroa-Colon et al, 1998;Oldroyd et al, 2003). In this study, precision values for body composition parameters are comparable with those reported by studies elsewhere, which have also used the iDXA.…”
Section: Resultssupporting
confidence: 81%
“…Elsewhere, and also using the more recent iDXA model, precision for TBL measurements have also been reported as excellent, with CVs of 0.4% (Rezzi et al, 2009), 0.52% (Faulkner et al, 2006) and 0.55% (Krueger et al, 2006).We also found excellent precision for the measurement of BMC, TBF and %TBF, compared with values reported elsewhere for older models of DXA and in a range of participants (Economos et al, 1997;Figueroa-Colon et al, 1998;Oldroyd et al, 2003). In this study, precision values for body composition parameters are comparable with those reported by studies elsewhere, which have also used the iDXA.…”
Section: Resultssupporting
confidence: 81%
“…DXA was performed at baseline, 8 weeks, and 16 weeks using a Hologic QDR2000 densitometer operating in array mode (Hologic, Waltham, MA, USA; software version 5.64A). This method has been validated against multi-compartmental methods and compared to in-vivo neutron inelastic scattering [8][9][10].…”
Section: Methodsmentioning
confidence: 99%
“…To overcome the systematic bias in DXA %fat measurement, we recommend the development of calibration models for DXA group mean %BF estimates in adolescent athletes, even though individual %BF estimates cannot be performed. The applicability of this recommendation to DXA instruments made by other manufacturers or to DXA instruments that use different scans modes and software is not known, though a few studies have shown a lack of interchangeability in DXA systems to assess soft tissue (Paton et al, 1995;Economos et al, 1997;Tothill et al, 1999;Tothill and Hannan, 2000).…”
Section: Validity Of Dual Energy X-ray Absorptiometrymentioning
confidence: 99%